Assessing the wood compressive strength in pile foundations in relation to diagnostic analysis: The example of the Church of Santa Maria Maggiore, Venice. (1st July 2016) - Pizzo, Benedetto; Macchioni, Nicola; Capretti, Chiara; Pecoraro, Elisa; Sozzi, Lorena; Fiorentino, Luigi
Graphical abstract: Highlights: The foundation piles of the Church of Santa Maria Maggiore, Venice, were investigated. The elements are still in service, and their mechanical properties were assessed. Loss for residual strength was greater than for decay-related residual mass. Both holocellulose decrease and mass loss contribute to the compressive strength reduction. Basic density and holocellulose could be used as possible predictors of residual strength. Abstract: Foundation piles are a noteworthy example of waterlogged wood still constituting load bearing structures. Micromorphological analysis, investigation of physical properties (water content, residual basic density), compressive tests in wet conditions and chemical analyses (lignin, holocellulose) were carried out on samples taken in Venice. Obtained results demonstrated that both mass and strength were lost due to decay, but the residual strength loss was greater than the residual mass. It is also shown that this occurrence was due to the holocellulose decrease. Present results point out that basic density and holocellulose amount could be used as possible predictors of woodpiles residual strength.